Do proactive career behaviours enhance individual well-being? An empirical study among professional engineers - Norizan Baba Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Engineers are very driven to go up the career tree, and they aim for psychological achievement. Nevertheless, the struggle between fulfilling the company’s work demands and having their ambitions and expectations affected their well-being. In Malaysia, engineers are reported as one of the groups of unhappy employees. Consequently, this research examines the impact of proactive career management behaviours (PCMB) on the personal well-being of Malaysian engineers. The current research involved 387 registered professional engineers from a variety of fields and businesses. The hypotheses were tested via a path analysis using PLS. The findings indicated a positive effect of PCMB on individual well-being. Employers and industries may use the results to incentivise their unlicensed engineers to enrol as graduates and pursue careers as professional engineers. For that reason, people will see their work as significant, thus increasing their work satisfaction.